Economic and non-economic variables affecting fraud in European Countries - Bashir Ahmad; Maria Ciupac-Ulici; Daniela-Georgeta Beju (Risks, 2021)
Fraud is one of the most harmful phenomena, because it leads to collapse of organizations, causes economic downfall of countries, and destroys faith in a country's capital markets. The impact of fraud is complex and has varying degrees depending on political and financial institutional structures of a country. In this paper, we investigate the combined effect of economic and noneconomic variables on fraud using a sample of 41 developed, in transition, and developing European countries. The data cover the period July 2014-December 2020. Panel data techniques of pooled estimation and the dynamic panel data/generalized method of moments (DPD/GMM) is used, keeping in view the endogeneity perspective. Nevertheless, two-way impacts of fixed effect model estimation-cross-sectional and time-based (panel) effects (alternatively)-are used for analyzing the relationship among the given variables, based on Hausman specification test results. Empirical results of panel data extended REM and FEM approaches with country-specific cross-sectional effects showing that political stability, economic freedom, poverty, and GDP significantly affect fraud proliferation. Political stability is appraised to be the most scoring determinant of fraud incidence in a country.
Keywords: 330; fraud; corruption; business operational risk; economic freedom; gross domestic product; political stability; poverty; type of governance; inflation; unemployment